2021
DOI: 10.1186/s12890-021-01399-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of anti-synthetase syndrome associated interstitial lung disease: a retrospective cohort in China

Abstract: Background Anti-synthetase syndrome (ASSD) is a chronic autoimmune condition characterized by antibodies directed against an aminoacycl transfer RNA synthetase (ARS) along with a group of clinical features including the classical clinical triad: inflammatory myopathy, arthritis, and interstitial lung disease (ILD). ASSD is highly heterogenous due to different organ involvement, and ILD is the main cause of mortality and function loss, which presents as different patterns when diagnosed. We desi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 32 publications
4
38
0
10
Order By: Relevance
“…The patient was subsequently found to have anti-EJ Ab using BlueDiver immunoblot kits (D-tek, Belgium) that measured each anti-ARS Ab separately. The frequency of anti-EJ Ab in ASS varies among previous studies, ranging from 1.8% to 23% [ 4 , 51 53 ]. Thus, Pinal-Fernandez et al investigated the frequency of anti-ARS Abs based on the Johns Hopkins Myositis Center cohort and demonstrated that anti-Jo1 Ab was most prevalent (73.4%) in ASS, followed by anti-PL12 (13.6%), anti-PL7 (9.5%), anti-EJ (1.8%), and anti-OJ (1.8%) Abs [ 51 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The patient was subsequently found to have anti-EJ Ab using BlueDiver immunoblot kits (D-tek, Belgium) that measured each anti-ARS Ab separately. The frequency of anti-EJ Ab in ASS varies among previous studies, ranging from 1.8% to 23% [ 4 , 51 53 ]. Thus, Pinal-Fernandez et al investigated the frequency of anti-ARS Abs based on the Johns Hopkins Myositis Center cohort and demonstrated that anti-Jo1 Ab was most prevalent (73.4%) in ASS, followed by anti-PL12 (13.6%), anti-PL7 (9.5%), anti-EJ (1.8%), and anti-OJ (1.8%) Abs [ 51 ].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, Hamaguchi et al reported that anti-EJ Ab was detected in 38 out of 166 Japanese patients with ASS (23%) [ 4 ]. As for its frequency in China, Zhan et al demonstrated that anti-EJ Ab was the third most prevalent anti-ARS Ab, preceded by anti-Jo-1 and anti-PL7 Abs in patients with ASS complicated by ILD with its frequency of 21% (23 out of 108 patients) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a large Chinese cohort, the spectrum varied from an OP pattern predominantly seen in anti-Jo1 positive ASyS with an NSIP pattern evident in anti-PL12 and anti-PL7. In anti-EJ patients, an OP pattern was most predominantly seen ( 35 ). Other smaller cohorts have shown overlap NSIP/OP patterns to be more prevalent in anti-Jo1 and anti-PL12 ( 36 ).…”
Section: Assessment Of Lung Diseasementioning
confidence: 98%
“…These include anti-Jo-1 (targeting histidyl tRNA synthetase), anti-PL7 (threonyl), anti-PL12 (alanyl), anti-OJ (isoleucyl), anti-KS (asparaginyl), anti-EJ (glycyl), anti-Zo (phenylalanyl), and anti-Ha (tyrosyl) antibodies (2)(3)(4). A single patient rarely produces multiple overlapping antibodies, so the antibodies in each patient result in the manifestation of unique clinical symptoms, progression, and a prognosis (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%